Pathophysiology and diagnosis of Guillain–Barré syndrome –challenges and needs. (1st June 2015) - Dash, Sambit; R. Pai, Aparna; Kamath, Ullas; Rao, Pragna
<x xml:space="preserve">Abstract</x> Guillain–Barré syndrome (GBS) is an autoimmune polyneuropathy which presents with acute onset and rapid progression of flaccid, hyporeflexi quadriparesis. Both sensory and autonomic nerve involvement is seen. GBS has various subtypes that vary in their pathophysiology. The pathogenesis involves an immune response triggered by a preceding event which may be an infection, immunisation or surgical procedure. Clinical diagnosis has been largely the primary diagnosing criterion for GBS along with electrodiagnosis, which has several pitfalls and is supported by ancillary testing of cerebrospinal fluid (CSF) analysis and Nerve Conduction Studies. Measurement of anti-ganglioside antibodies is also an effective tool in its diagnosis. Further understanding of pathophysiology and better diagnostic methods are required for better management of GBS.